1981
DOI: 10.1159/000299595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crude and Purified Human Chorionic Gonadotropin on Lymphocyte Response

Abstract: Human chorionic gonadotropin (hCG) preparations with different biological activities were tested for their inhibitory effects on mitogenic of allogenic induced lymphocyte response. Various crude hormone batches inhibited the lymphocyte reaction in a dose-dependent manner. However, we found a varying suppression of lymphocyte response not correlated to the biological activity (2,660–4,300 IU/mg) of crude hormone. Fractions with very low gonadotropic activity ( < < 500 IU/mg) showed a 100-fold inhibition of lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In 1973, crude HCG purified from urine was reported to suppress immune reactions 91 . Subsequent studies demonstrated that contaminating factors other than HCG are responsible for these effects and highly purified HCG had no effect on lymphocyte function 92–94 . Thereafter, the secretion of several cytokines was shown to be modified by HCG stimulation in PBMC in vitro 95–97 .…”
Section: Dual Signaling Mechanisms To Endocrine and Immune Systems Bymentioning
confidence: 99%
“…In 1973, crude HCG purified from urine was reported to suppress immune reactions 91 . Subsequent studies demonstrated that contaminating factors other than HCG are responsible for these effects and highly purified HCG had no effect on lymphocyte function 92–94 . Thereafter, the secretion of several cytokines was shown to be modified by HCG stimulation in PBMC in vitro 95–97 .…”
Section: Dual Signaling Mechanisms To Endocrine and Immune Systems Bymentioning
confidence: 99%